Smarcb1 loss results in a deregulation of esBAF binding and impacts the expression of neurodevelopmental genes - Alfert, Amelie; Walter, Carolin; Moreno, Natalia; Melcher, Viktoria; Graf, Monika; Hotfilder, Marc; Dugas, Martin; Albert, Thomas; Kerl, Kornelius (Cells, 2022)
The murine esBAF complex plays a major role in the regulation of gene expression during stem cell development and differentiation. As one of its core subunits, Smarcb1 is indispensable for its function and its loss is connected to neurodevelopmental disorders and participates in the carcinogenesis of entities such as rhabdoid tumours. We explored how Smarcb1 regulates gene programs in murine embryonic stem cells (mESC) and in this way orchestrates differentiation. Our data underline the importance of Smarcb1 expression and function for the development of the nervous system along with basic cellular functions, such as cell adhesion and cell organisation. Using ChIP-seq, we were able to portray the consequences of Smarcb1 knockdown (kd) for the binding of esBAF and PRC2 as well as its influence on histone marks H3K27me3, H3K4me3 and H3K27ac. Their signals are changed in gene and enhancer regions of genes connected to nervous system development and offers a plausible explanation for changes in gene expression. Further, we describe a group of genes that are, despite increased BAF binding, suppressed after Smarcb1 kd by mechanisms independent of PRC2 function.